Identifying indigenous practices forcultivation of wild saprophytic mushrooms:responding to the need for sustainableutilization of natural resources - Wendiro, Deborah (2019)
Background: Due to increasing pressure on natural resources, subsistence agriculture communities in Uganda and Sub-Saharan Africa are experiencing increasingly restricted access to diminishing natural resources that are a critical requirement of their livelihoods. Previously, common-pool resources like forests and grasslands have been either gazetted for conservation or leased for agriculture, the latter in particular for large-scale sugarcane production. Satisfying the increasing consumer demand for grassland or forestry products like wild mushrooms as food or medicine, requires innovative ethno-biological and industry development strategies to improve production capacity, while easing the pressure on diminishing natural resources and averting ecosystems degradation. Methods: This case study addresses traditional knowledge systems for artisanal mycoculture to identify cultivation practices that enhance sustainable utilization of natural resources. Multi-scalar stakeholder engagement across government and community sectors identified artisanal mushroom producers across five districts in Uganda. Focus groups and semi-structured interviews characterized artisanal production methods and identified locally used substrates for cultivation of different mushroom species. Results: Artisanal practices were characterized for the cultivation of six wild saprophytic mushroom species including Volvariella speciosa (akasukusuku), two Termitomyces sp. (obunegyere and another locally unnamed species), Agaricus sp. (ensyabire) and Agrocybe sp. (emponzira), and one exotic Pleurotus sp. (oyster) that are used as food or medicine. The substrates used for each species differed according to the mushroom’s mode of decomposition, those being the following: tertiary decomposers such as those growing under rotting tree stumps or logs from forestry activity like the Agrocybe sp. known as emponzira which grows in forests, thickets, or near homesteads where big logs of hardwood have been left to rot. Also pieces of firewood are chipped off whenever need arises thus providing fuel; secondary decomposers growing on naturally composted grass associated with termites like the Termitomyces sp. known as obunegyere growing in protected sites in gardens, composted cattle manure for Agaricus sp. known as ensyabire in the kraal area where cattle manure is plenty, composted maize cobs for a locally unnamed Agaricus sp. on heaped cobs placed near homesteads; and primary decomposers growing on waste sorghum from brewing the traditional alcoholic drink, muramba for Pleurotus sp. (oyster), and banana and spear grass residue from banana juice processing like the Volvariella speciosa known as akasukusuku because it is associated with the banana plantation locally known in the Luganda language as olusuku and is usually heaped...